Hybrid Graph Representation and Learning Framework for High-Level Synthesis Design Space Exploration - Pouya Taghipour; Eric Granger; Yves Blaquiere (IEEE Access)
Optimizing hardware accelerators in high-level synthesis (HLS) relies on design space exploration (DSE), which involves experimenting with different pragma options and trading off hardware cost and performance metrics (HCPMs) to identify Pareto-optimal solutions. The exponential growth of the design space, poor quality-of-results (QoR) estimation by HLS tools, and lengthy post-implementation runtime have made the HLS DSE process highly challenging and time-consuming. Automating this process could reduce time-to-market and associated development costs. Learning-based methods, particularly graph neural networks (GNNs), have shown considerable potential in addressing HLS QoR/DSE problems by modeling the mapping function from control data flow graphs (CDFGs) of HLS designs to their logic, enabling early estimation of QoR during the compilation phase of the hardware design flow. However, there is still a gap in terms of their prediction accuracy. Indeed, modeling HLS-related problems using GNNs that efficiently capture the complex patterns arising from applied pragmas and low-level characteristics of HLS specifications is challenging. This paper introduces a novel hybrid graph representation and learning framework under a multi-task setting, featuring two distinct types of CDFGs derived from two different sources. Furthermore, various models are proposed to fuse features and knowledge in joint, sequential, and parallel learning architectures, aiming to improve the overall accuracy and generalization in predicting QoR and approximating the Pareto frontier (PF). Experimental results show that our framework can attain a higher level of performance than the state-of-the-art baseline models over unseen designs, with an average relative improvement of 47.4 % and 16.0 % for resource utilization and performance metrics, respectively. Additionally, considering various HLS designs with different design space sizes, a 26.8 % enhancement in DSE PF approximation is observed.